Cellulose nanofiber as nucleating agent and reinforcement material in improving crystallization and mechanical properties of polylactic acid nanocomposites - Shamsudin, Siti Shazra Shazleen (2021)
Polylactic acid (PLA) is one of the most utilized biodegradable polymer to replace petroleum-based polymer. However, PLA has a slow crystallization rate which has a negative impact on its melt processing, hence limiting the application of PLA in industry. The reinforcement of cellulose nanofiber (CNF) within the PLA matrix can enhance the mechanical properties of nanocomposites, but the nucleation effect of CNF on the crystallization behavior, particularly the crystallization rate, remains unclear. In this study, PLA nanocomposites consisted of 1 – 6 wt% CNF (PLA/CNF1-PLA/CNF6) were prepared by melt blending method, and the crystallization kinetic behavior of the PLA and PLA/CNF nanocomposites were determined by DSC analysis. In the nonisothermal crystallization study, it was found that PLA/CNF3 exhibited the highest crystallization onset temperature and enthalpy among all the PLA/CNF nanocomposites. PLA/CNF3 also had the highest crystallinity of 44.2% with an almost 95% increment than neat PLA. The highest crystallization rate of 0.716 min-1 was achieved when PLA/CNF3 was isothermally melt crystallized at 100°C. The crystallization rate was 65-fold higher as compared to the neat PLA (0.011 min-1). At CNF wt% higher than 3%, the crystallization rate reduced, suggesting the occurrence of agglomeration at higher CNF loading. PLA-g-MA was used as compatibilizer to improve interfacial adhesion between CNF and PLA. Results showed that the PLA-g-MA has some effect on nucleation, in which the crystallization half time for PLA-g-MA reduced to 33.2 min compared to neat PLA when isothermally melt crystallized at 100°C. Nevertheless, the presence of PLA-g-MA in PLA/PLA-g-MA/CNF3 nanocomposites did not improve the crystallization rate as compared to PLA/CNF3, indicating that the use of PLA-g- MA as compatibilizer may not be necessary in order to improve the crystallization kinetic of PLA nanocomposites. Tensile strength and Young’s modulus of the PLA/CNF nanocomposites increased with CNF incorporation up to 5 wt%, without the use of any compatibilizer. The highest tensile strength and Young’s modulus of 76.1 MPa and 3.3 GPa, respectively, were recorded at 4 wt% CNF. These were higher than those of neat PLA (70.6 MPa and 2.9 GPa). This shows that CNF is an effective reinforcement material for PLA. When PLA-g-MA was used, the tensile strength was lower compared to the nanocomposite without compatibilizer. The tensile strength was found reduced with the increased amount of PLA-g-MA. On the other hand, Young’s modulus increased drastically to 11 GPa in the presence of compatibilizer, suggesting the rigidity of the nanocomposites when PLA-g-MA was used. The combination of CNF nucleation and PLA-g-MA compatibilization did not influence the crystallite size of the PLA nanocomposites. The addition of CNF and PLA-g-MA into PLA also did not have much effect on the thermal stability, despite of slight reduction in thermal degradation temperature. It was evident that the presence of PLA-g-MA in PLA/CNF nanocomposites did not improve the crystallization kinetic and mechanical properties. These findings affirm the role of CNF as an effective nucleating agent and simultaneously act as a nano-reinforcement material in enhancing the crystallization and mechanical properties of PLA. Thus, it is possible to manufacture higher quality biodegradable nanocomposites that is eco-friendlier and more sustainable in the future.